2013
DOI: 10.1590/s0100-06832013000200002
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogy of the clay fraction of alfisols in two slope curvatures: IV - spatial correlation with physical properties

Abstract: SUMMARYAlthough the influence of clay mineralogy on soil physical properties has been widely studied, spatial relationships between these features in Alfisols have rarely been examined. The purpose of this work was to relate the clay minerals and physical properties of an Alfisol of sandstone origin in two slope curvatures. The crystallographic properties such as mean crystallite size (MCS) and width at half height (WHH) of hematite, goethite, kaolinite and gibbsite; contents of hematite and goethite; aluminiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
(50 reference statements)
0
7
0
Order By: Relevance
“…For this purpose, geostatistical techniques are used to study the spatial variability of soil and plant properties (Zanão Júnior et al, 2007;Marins et al, 2008;Vieira et al, 2011;Campos et al, 2012Campos et al, , 2013Camargo et al, 2013;Bottega et al, 2013). However, these techniques require a previous sample design with the exact spatial position of each sample point (Montanari et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, geostatistical techniques are used to study the spatial variability of soil and plant properties (Zanão Júnior et al, 2007;Marins et al, 2008;Vieira et al, 2011;Campos et al, 2012Campos et al, , 2013Camargo et al, 2013;Bottega et al, 2013). However, these techniques require a previous sample design with the exact spatial position of each sample point (Montanari et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…2). The soluble Si contents should also be associated with the type of soil and not just to the soil clay content because there are mineralogical differences among highly-weathered soils, such as Oxisols and Ultisols in the case of this study, mainly related to the quantity of oxides, oxi-hydroxides and silicated minerals in their surface horizons 5155 , that probably result in available Si contents not simply explained by soil clay content 10 . A previous study using four types of soil (Typic Udorthent, Ultisol, Oxisol and Udox) demonstrated a negative correlation between the soil clay and soluble Si contents only in the Ultisol 29 , which agreed with the results of this study.…”
Section: Discussionmentioning
confidence: 83%
“…Qualitative and quantitative soil mineralogy, as well as weathering stage, SiO 2 contents and pH values, around both municipalities Guaíra and Ariranha, can be found in Alves and Lavorenti 51 , Soares et al . 52 , Alves and Omotoso 53 , and Camargo and Marques Júnior 54,55 . The soil minerals consist essentially of kaolinite, hematite, goethite, gibbsite and quartz.…”
Section: Methodsmentioning
confidence: 99%
“…The mineralogical composition of Brazilian Ultisols include varying proportions of iron oxides, gibbsite, and kaolinite, which in turn are related to the soil's physical attributes (Lu et al, 2014;Bonetti et al, 2017). Furthermore, Camargo et al (2013) and Ramos et al (2015) found high values of soil bulk density and penetration resistance in kaolinitic soils. Meanwhile, Manyala et al (2015) and Wu et al (2016) showed a correlation between BD and iron extracted by dithionitecitrate-bicarbonate (DCB) in Ultisols.…”
Section: Introductionmentioning
confidence: 99%